2023
DOI: 10.1007/s00415-023-11692-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection after SARS-CoV-2 mRNA vaccination in Multiple Sclerosis, AQP4-antibody NMOSD and MOGAD patients during the Omicron subvariant BA.1/2 wave in Singapore

Abstract: Background The SARS-CoV-2 Omicron variant appears to cause milder infections, however, its capacity for immune evasion and high transmissibility despite vaccination remains a concern, particularly in immunosuppressed patients. Herein, we investigate the incidence and risk factors for COVID-19 infection in vaccinated adult patients with Multiple Sclerosis (MS), Aquaporin-4-antibody Neuromyelitis Optica Spectrum Disorder (AQP4-Ab NMOSD), and Myelin Oligodendrocyte Glycoprotein-antibody associated disease (MOGAD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The prevalence of COVID‐19 in NMOSD patients was found to be 1.2% till July 2021 12 . A Singaporean study found COVID‐19 Omicron BA.1/2 wave infection in vaccinated patients with MS, NMOSD, and MOGAD was 23.4% over a 4‐month period 13 . 85.7% of NMOSD patients reported that had developed COVID‐19 clinical symptoms in our study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of COVID‐19 in NMOSD patients was found to be 1.2% till July 2021 12 . A Singaporean study found COVID‐19 Omicron BA.1/2 wave infection in vaccinated patients with MS, NMOSD, and MOGAD was 23.4% over a 4‐month period 13 . 85.7% of NMOSD patients reported that had developed COVID‐19 clinical symptoms in our study.…”
Section: Discussionsupporting
confidence: 49%
“… 12 A Singaporean study found COVID‐19 Omicron BA.1/2 wave infection in vaccinated patients with MS, NMOSD, and MOGAD was 23.4% over a 4‐month period. 13 85.7% of NMOSD patients reported that had developed COVID‐19 clinical symptoms in our study. Despite the relatively high prevalence rate in our cohort, there is no difference between NMOSD group and HC group.…”
Section: Discussionmentioning
confidence: 51%
“…In particular, both antibody production and memory B cell responses were impaired when treated with anti-CD20 antibodies. Both humoral and T cell responses were also diminished in patients treated with S1P-r modulators [8,[18][19][20]. Accordingly, we found an approximately two-fold increased risk to contract SARS-CoV-2 infection in vaccinated MS patients who were treated with anti-CD20 at time of vaccination.…”
Section: Discussionmentioning
confidence: 56%